Interfaces físicas entre os sistemas prediais hidráulicos e sanitários (SPHS), estruturais e vedações - Boni, Adriana Cristina (2010)
The identification and resolution of interfaces is a requirement that must be met for additional methods for evaluating design for Hydraulic and Sanitary Building Services (plumbing systems). The reason is that these building systems, in general, may have a higher incidence of problems of compatibility with others, because they all relate to. In this context, this work aims to identify the main physical interfaces among the plumbing systems, masonry and structures systems, which occur in the pavement type of residential multistory buildings. The building system of fuel gas is also discussed, because it works in conjunction with cold water system in these buildings. Physical interfaces are considered: between plumbing systems and non-loadbearing walls or structural masonry; and between the plumbing systems and masonry structures and reinforced concrete cast on site. For this literature review was performed and case studies in the cities of Ribeirão Preto, São Carlos and São Paulo, comprising six companies and two buildings (units of analysis). Of the companies surveyed, two are construction and incorporation companies (the contractors). Four companies are design offices (contracted), two specialized in plumbing systems, one in masonry structure, and one architectural design offices specializing in non-loadbearing walls. The literature review is related to the main recommendations of the Brazilian technical standards and with the necessary information for the design phases, referring to the interfaces of the systems mentioned. The case studies resulted in findings that identified the compliance and nonconformities resulting from physical interaction among the various designs necessary for the production of buildings. Through these case studies, it was still possible to develop a matrix for the interfaces found on the pavement type, and relating them to main stages of the design. The results of this study can allow feedback from the design stage, thus contributing to the same quality as the product.